Effect of the peer teaching learning model on Sickle kick and pencak silat t kick - Moh Sabilillah; Dinar Dinangsit; Dewi Susilawati (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
The purpose of this study was to determine the extent of the impact of peer teaching learning methods on the ability of the sickle kick and the T-kick of pencak silat. The population in this study was the Pencak Silat Athletes of the Indonesian Satria Muda College of Cirebon City with total sampling technique with a total of 25 people. The instrument in this study is the Peer Teaching Learning Model, measuring kick skills to measure the ability of the sickle kick and T kick skills before and after being given treatment, namely the peer teaching learning model. The results showed that there was a significant increase in the ability of the sickle kick and T kick skills in athletes after being given treatment